Knowledge of health benefits, availability, accessibility and consumption of indigenous foods by urban adults in the Cape Metropole, South Africa - Tasneem Johnson; Mthokozisi Zuma; Laurencia Govender; Nelene Koen; Xikombiso Mbhenyane (PLoS ONE, 2025)
Background Indigenous foods are effective in addressing malnutrition and food insecurity and contain phytochemicals which have been reported to prevent non-communicable diseases. Understanding the role that indigenous foods play can add to our understanding of how to promote these foods within urban communities of South Africa. Aim To describe the knowledge of health benefit, availability, accessibility, perceptions and consumption regarding South African indigenous foods. Methods A cross-sectional study design was used. Data was collected using a managerial survey (n = 5), observational checklist (n = 27), consumer survey (n = 43) and household survey (n = 344). Adults between 18 and 80 years residing in the Cape Metropole participated. Results Most of the household’s population had a low-medium dietary diversity (65.8%). Perceptions regarding indigenous foods were mostly favourable, with economic and nutritional benefits and the quality reported as being key aspects. Indigenous foods were reported to be most available from supermarkets (69.0%) as opposed to grocery stores (19%) or food stalls (8.0%). Samp, maize meal and pumpkin observed at food establishments were seen to be the most accessible indigenous food items. Many households (57.6%) fell below the monthly income required to ensure food security. Only 58.8% and 47.2% of household participants reported knowing indigenous foods and their health benefits, respectively. Conclusion The study population demonstrated limited knowledge regarding the definition and health benefits of IFs. Within the Cape Metropole, IFs were perceived as largely unavailable and inaccessible across food establishments. Additionally, there was a common misconception equating IFs with exotic foods. Despite this confusion, a significant proportion of participants expressed a willingness to purchase IFs if they were more readily accessible.